The Dilemma of Handling Cases of Child Copulation: Obstacles, Strategies, and Gorontalo Protection - Mointi, Nurul Ananda Sahwa; U. Puluhulawa, Moh. Rusdiyanto; Apripari, Apripari; Devi, Sri (Universitas Negeri Gorontalo, 2025)
Cases of sexual intercourse involving minors are one of the legal challenges that require serious attention, both in terms of prosecution and protection of children's rights. The public prosecutor plays a key role in the prosecution of these cases, not only in drafting the indictment and laying charges, but also in safeguarding the rights of children as victims and perpetrators. This study aims to analyze the role of public prosecutors in the prosecution of cases of child sexual intercourse and the obstacles faced in the prosecution process. The research method used is a qualitative approach with an empirical study, collecting data through interviews with public prosecutors and other related parties, as well as analyzing case documents. The results showed that prosecutors at the Gorontalo District Public Prosecutor's Office faced a number of internal obstacles, such as limited human resources competent in handling juvenile cases, as well as a lack of training related to child psychology and rehabilitative approaches. In addition, external obstacles faced are the legal culture of the community that does not fully support the protection of children's rights, as well as the social stigma against children involved in criminal acts. This study suggests the need for increased training for prosecutors in handling children's cases, as well as the importance of socialization to the community regarding the protection of children's rights. With these efforts, it is hoped that the prosecution of child sexual abuse cases can be more effective and fair.